Comportamiento de los depósitos y créditos en el sistema financiero en las regiones de selva baja del Perú periodo 2020 - 2021 - Gomez Reyes, Francisco Miguel (2022)
The financial sector is made up of the banking sub-sector and the non-banking sub-sector, within the banking entities, multiple banking stands out for having a greater participation in both deposits and loans and within the non-banking, the Municipal Savings Banks maintain leadership for having more deposits and more credits awarded. The work "BEHAVIOR OF DEPOSITS AND CREDITS IN THE FINANCIAL SYSTEM IN THE REGIONS OF SELVA BAJA DEL PERU PERIODO 2020 - 2021" includes the regions of Loreto and Ucayali, its general objective is to determine the growth of deposits and credits in the financial system in the low jungle regions of Peru, period 2020 - 2021, the research is of an applied type with a quantitative approach at a descriptive level and a non-experimental design. The results show that both in the Loreto and Ucayali regions, the behavior has varied from month to month in both deposits and loans, with growth in some months and decreases in others; the Loreto region has higher amounts of deposits and credit placement than the Ucayali region; At the end of 2021, Loreto has a balance in deposits of 1,770 million soles and in loans 2,598 million soles, while Ucayali has a balance in deposits of 1,360 million soles and in loans 2,014 million soles.